2021
DOI: 10.1038/s41598-021-92264-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an adipose-liver human-on-a-chip model of NAFLD for preclinical therapeutic efficacy evaluation

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease and strongly correlates with the growing incidence of obesity and type II diabetes. We have developed a human-on-a-chip model composed of human hepatocytes and adipose tissue chambers capable of modeling the metabolic factors that contribute to liver disease development and progression, and evaluation of the therapeutic metformin. This model uses a serum-free, recirculating medium tailored to represent different human metabolic condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…As a bionic technology, the organ-on-a-chip can accurately control biochemical factors, mechanical stress, and other parameters, thereby simulating the smallest functional unit of human organs in vitro [ 23 , 37 ]. In addition, the organ-on-a-chip also has the characteristics of low loss, high throughput, and integration, so it is regarded as a bionic, energy-saving, and efficient platform that can be used for physiology research and drug development [ 24 , 26 ]. The designed liver cancer-on-a-chip included a concentration gradient module and a drug response module.…”
Section: Resultsmentioning
confidence: 99%
“…As a bionic technology, the organ-on-a-chip can accurately control biochemical factors, mechanical stress, and other parameters, thereby simulating the smallest functional unit of human organs in vitro [ 23 , 37 ]. In addition, the organ-on-a-chip also has the characteristics of low loss, high throughput, and integration, so it is regarded as a bionic, energy-saving, and efficient platform that can be used for physiology research and drug development [ 24 , 26 ]. The designed liver cancer-on-a-chip included a concentration gradient module and a drug response module.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, the advancements made to the development of “human-on-a-chip” models seem as effective strategies for testing novel drug candidates. The system provides a simple but unique platform to evaluate preclinical drug efficacy and reassess human dosing regimens [ 317 , 318 ]. Moreover, by implementing in these chips, patient-derived stem cells carrying high-risk genetic backgrounds for developing NASH, the evaluation of personalized therapies might ever become a reality [ 319 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using this device, Lee and Sung showed that butyrate, a compound known to enhance the gut barrier function, attenuated lipid accumulation; a benefit not observed when the drug was tested on hepatocytes alone. Recently, Slaughter et al. (2021) developed a body-on-a-chip with adipose and liver tissue, to evaluate the mechanisms involved in NAFLD development and serve as a drug screening platform.…”
Section: D Tissue Culture Models In Nafldmentioning
confidence: 99%